2010
DOI: 10.1104/pp.110.165910
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-Genetic Analysis of the Two Biotin-Containing Subunit Genes of the Heteromeric Acetyl-Coenzyme A Carboxylase in Arabidopsis Indicates a Unidirectional Functional Redundancy      

Abstract: The heteromeric acetyl-coenzyme A carboxylase catalyzes the first and committed reaction of de novo fatty acid biosynthesis in plastids. This enzyme is composed of four subunits: biotin carboxyl-carrier protein (BCCP), biotin carboxylase, a-carboxyltransferase, and b-carboxyltransferase. With the exception of BCCP, single-copy genes encode these subunits in Arabidopsis (Arabidopsis thaliana). Reverse-genetic approaches were used to individually investigate the physiological significance of the two paralogous B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 85 publications
1
60
0
Order By: Relevance
“…The BCCP1 transcript is expressed constitutively, while BCCP2 is predominant in flowers and siliques and its overall abundance is approximately 4-fold lower than that of BCCP1 (Thelen et al, 2000). The development of the endosperm and embryo is disrupted when BCCP1 is knocked-out during Arabidopsis seed development, and fatty acid accumulation decreases and normal vegetative plant growth is severely affected when BCCP1 accumulation is reduced at the protein level (Li et al, 2011). These results indicate that BCCP genes are involved in de novo lipid synthesis storage and accumulation (Elborough et al, 1996;Thelen et al, 2000;Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The BCCP1 transcript is expressed constitutively, while BCCP2 is predominant in flowers and siliques and its overall abundance is approximately 4-fold lower than that of BCCP1 (Thelen et al, 2000). The development of the endosperm and embryo is disrupted when BCCP1 is knocked-out during Arabidopsis seed development, and fatty acid accumulation decreases and normal vegetative plant growth is severely affected when BCCP1 accumulation is reduced at the protein level (Li et al, 2011). These results indicate that BCCP genes are involved in de novo lipid synthesis storage and accumulation (Elborough et al, 1996;Thelen et al, 2000;Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
“…The production of malonyl-CoA catalyzed by ACCase is the rate-limiting step in the process of fatty acid biosynthesis (Thelen et al, 2000;Fukuda et al, 2013). Previous studies have confirmed that heteromeric ACCase plays an important regulatory function during oil synthesis and accumulation in plant seeds (Thelen et al, 2000;Dong et al, 2004;Hu et al, 2009;Liu et al, 2009;Li et al, 2011). Homomeric ACCase is composed of a large multifunctional polypeptide (Sasaki and Nagano, 2004) and heteromeric ACCase is composed of a biotin carboxyl carrier protein (BCCP), biotin carboxylase (BC), and carboxyltransferase (CT), which consists of α-and β-subunits.…”
Section: Introductionmentioning
confidence: 99%
“…BCCP1 is an essential subunit for a heteromeric acetylCoA carboxylase, which catalyzes the ATP-dependent formation of malonyl-CoA in the first committed step of the FA biosynthetic pathway (Ohlrogge and Browse, 1995). Down-regulation of BCCP1 decreases FA accumulation in seeds and severely affects normal vegetative plant growth (Li et al, 2011). The down-regulation of KAR5 and BCCP1 expression in siliques (2 DAF) may explain the decreased FA accumulation in tt16 RNAi transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…The BCCP1 isoform is constitutively expressed, while BCCP2 is predominantly expressed in the seed under the control of the WRINKLED1 transcription factor (Thelen et al, 2001;Ruuska et al, 2002;. Of these two isoforms, BCCP2 was shown to be more active in vitro (Thelen et al, 2001) but nonessential to plant growth (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%